2022
DOI: 10.1186/s12981-021-00425-0
|View full text |Cite
|
Sign up to set email alerts
|

Routine HIV clinic visit adherence in the African Cohort Study

Abstract: Background Retention in clinical care is important for people living with HIV (PLWH). Evidence suggests that missed clinic visits are associated with interruptions in antiretroviral therapy (ART), lower CD4 counts, virologic failure, and overlooked coinfections. We identified factors associated with missed routine clinic visits in the African Cohort Study (AFRICOS). Methods In 2013, AFRICOS began enrolling people with and without HIV in Uganda, Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Though the distance to the clinic, according to the study, was not significant to viral suppression (P>0.43), it was greatly significant with adherence to medication (P<0.001). This was consistent with studies carried out in Uganda [23], in Kenya, Nigeria and Tanzania [24]. The social conditions surrounding a patient on ART and the availability of food were found to be determinant of adherence and, thus viral suppression.…”
Section: Discussionsupporting
confidence: 89%
“…Though the distance to the clinic, according to the study, was not significant to viral suppression (P>0.43), it was greatly significant with adherence to medication (P<0.001). This was consistent with studies carried out in Uganda [23], in Kenya, Nigeria and Tanzania [24]. The social conditions surrounding a patient on ART and the availability of food were found to be determinant of adherence and, thus viral suppression.…”
Section: Discussionsupporting
confidence: 89%
“…The high volume of patients relative to the few healthcare workers compromises on the quality of client-healthcare worker interaction, privacy, poor quality of care, and failure of the healthcare workers to identify issues of ART adherence among clients [28]. Measures should be developed to reduce long waiting times in ART clinics so as to reduce issues of non-adherence to medications and consequent treatment failure Consistent with findings from previous studies [28,29], poverty, and low-socio economic status contributed to the ART non adherence among HIV young adults. In a scoping review of the factors contributing to ART adherence, logistical and financial support to HIV positive clients were found to facilitate adherence to ART medication [30], which also supports our findings.…”
Section: Discussionsupporting
confidence: 53%
“…Our subgroup analyses showed that among care recipients who had been on treatment for <90 days, loss aversion messages were effective in promoting timely clinic attendance. This is notable since research shows that care recipients who miss visits within the first six months on treatment have increased likelihood of poor outcomes (22,24). Care recipients who have been on treatment for >90 days may have become accustomed to clinic messages or may feel it is less important to come to the clinic on or before the scheduled appointment date especially if they still have medication in hand.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it could be that reasons for not having timely clinic attendance have been due to structural and economic barriers such as high transportation costs, opportunity costs of time, or long clinic wait times. These barriers have been shown to significantly impact clinic attendance, particularly for marginalized and underserved populations (22,23), and they are less likely to be addressed by text messages. Third, the lack of timely clinic attendance may be due to the perception of a scheduled clinic visit date as merely being a suggested date to come to the clinic rather than an exact appointment date.…”
Section: Discussionmentioning
confidence: 99%